Evaluation of outpatient health services in diabetes mellitus in a middle-income setting: a retrospective cohort study involving secondary care - Oliveira, Felipe Martins de; Chiaradia, Caio; Zaia, Silvana Marques; Ordonha, Ana Carolina Xavier; Garcia, Sônia Aparecida Dias; Reis, Ligia Dinara Donizeti; Ribeiro, Manoel Carlos Sampaio de Almeida; Salles, João Eduardo Nunes (Acta Scientiarum. Health Sciences, 2023)
In Brazil, it is necessary to assess the different levels of health care in diabetes mellitus (DM) in order to integrate them. In this retrospective cohort study, we analyzed 1,122 medical records of patients with DM from specialized services with interdisciplinary health teams (IHT) in the city of Ourinhos, São Paulo state, Brazil, to assess the impact of secondary care on glycemic control in patients with DM in those places and to compare baseline and follow-up DM care indicators concerning clinical evaluation and drug treatment regimens in the aforementioned health services. The study covered consultations carried out from September/2013 to September/2017. Data were collected from initial and final appointments in medical records and revealed an increase of 31.21% in insulin introduction and of 73.53% in regimens with three or more non-insulin antidiabetic (NIA) medications. Among the 570 patients with at least two glycated hemoglobin (A1C) measurements in the aforementioned review, 146 did not require any therapeutic adjustment between initial and final appointments, 123 required a subtle adjustment, 95, a moderate adjustment, and 206, an intense adjustment. There was a noticeably higher A1C reduction between initial and final appointments when patients who required an intense drug adjustment were compared to those who did not need any different NIA drug (p-value < 0.0001). In addition to optimizing drug treatment, essential exams in DM were performed with higher frequency, with an increase of 63% in ophthalmology evaluation performed during secondary care approach and 60.65% more individuals being screened for diabetic chronic kidney disease. IHT secondary care considered in this study, therefore, not only improved glycemic control of patients with DM, especially by optimization of NIA regimens and timely prescription of insulin, but also increased the screening for microvascular complications.